Prevotella intermedia and Porphyromonas gingivalis isolated from osseointegrated dental implants: colonization and antimicrobial susceptibility - Pfau,Eduardo Augusto (2005)
The colonization and antimicrobial susceptibility of P. intermedia and P. gingivalis isolated from peri-implant and gingival sulcus samples were determined. Samples were collected from 30 patients submitted to implant in three different times: at the moment of the surgery, 20 and 60 days after the implant installation. Organisms were identified by using a biochemical tests or API 32-A kit and by PCR. The antimicrobial susceptibility was determined by using an agar dilution method. Nineteen P. intermedia (4 from peri-implant sites and 15 from gingival sulcus), and only seven P. gingivalis from gingival sulcus were isolated. Organisms were detected by PCR from seven peri-implant and 32 gingival samples. Bacteria were susceptible to the used antibiotics except to azithromycin with 65% of resistance for P. intermedia strains. Both tested species were susceptible to cadmium, nickel and palladium, and showed different resistance rates to titanium, aluminum and mercuric chloride. Most of P. intermedia strains were resistant to lead, silver, copper, titanium, zinc, aluminum and mercuric chloride. Bacteria colonized implants after 60 days of surgery and PCR may be used as a tool for bacterial detection in implantology.